The role of internal audit standardization in improving the audit quality - Sitenko, D.A.; Shakirova, G.A.; Nurgaliyeva, G.K. (BUKETOV BUSINESS REVIEW, 2021)
Object: The object of the article is to consider the issues of building an internal audit and control system based on international standards of internal audit. Methods: The research used the methods of system analysis, comparative analysis, grouping method, content analysis. Findings: As a result of the study, the relationship between the goals of the organization, risks and controls in internal audit was determined. The most likely areas of risk during the audit were identified. It has been shown that the most useful for the company are controls that identify and prevent negative events for the company before they occur. Possible directions of use of international standards for the professional practice of internal auditing (International Professional Practices Framework (IPPF) in the development of internal auditing standards of an organization have been identified. A range of standards that can be developed on the basis of the IPPF in the organization is determined. The content and structure of applied standards based on the IPPF for internal audit of an enterprise are proposed. Conclusions: The application of international standards in auditing allows an organization to implement a systematic and consistent approach to the audit process. The development of internal standards of an organization based on international ones will help to improve the accuracy of the assessment of control procedures at each stage of verification, to solve problems in the field of risk management and to increase the efficiency of business processes.